(3GdeNJGQ ef TYQ CHj aQGS GdMeOGfis - (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s
(3ChdgG (B:s
(3GdTYQ OjhGf GdYQH CHOkG hYfhGf GdCOH s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi Hbhd GdNGdY (B_ (3CKfGA bUI (B: (3dg HGdgeGe GHf GdeYeQ aJcI hai GdSja ajgG hGdQeGM ZhGOQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3OjhGf TYQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B156s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs